Phytochemical Evaluation and Lethal Concentration of Aqueous Extract of Adansonia digitata Fruit Pulp in Clarias gariepinus - Abdulsalam, Hassan; Sani, Dahiru; Chiroma, Mohammed A.; Gadzama, Joseph J.; Tijani, Adams A.; Salihu, Sabo I.; Maidala, Hussaina M.B.; Usman, Bello; Sambo, Sohnap J.; Adamu, Sani (Sahel Journal of Life Sciences FUDMA, 2024)
The study was aimed at assessing the lethal concentration 50 (LC50) of aqueous extract of Adansonia digitata fruit pulp (AEADFP) in Clarias gariepinus. Adansonia digitata fruit pulp was obtained at the Faculty of Veterinary Medicine, Ahmadu Bello University (A.B.U), Zaria, Nigeria. Proximate nutrient composition was determined according to the Association of Official Analytical Chemist. Maceration method was employed for Adansonia digitata fruit pulp extraction using distilled water, and thereafter, screened for phytochemical constituents. A total of 200 African catfish (Clarias gariepinus) weighing between 185 ± 5 g (27-36 cm) were used for determination of LC50 of AEADFP using standard procedure at the aquaculture animal house Unite of Department of Veterinary Pathology, A.B.U., Zaria. Twenty (20) fish were used for range finding test, while 180 fish for LC50 evaluation. The experimental fish were observed for clinical signs of toxicity and mortality. The result of proximate nutrient composition of Adansonia digitata fruit revealed the presence of carbohydrate, lipid, protein, ash, moisture, and crude fiber. Qualitative phytochemical evaluation revealed the presence of tannins, flavonoids, phenol, terpenoid, glycosides, saponins, anthraquinone, steroids, reducing sugar and alkaloids, while quantitative phytochemical assay showed that total Phenol and alkaloid had highest and lowest concentration, respectively. There was neither mortality nor any clinical sign of toxicity observed for the 96 hours post-administration to AEADFP up to 5000 mg/L. Conclusively, AEADFP had nutritional and bioactive compounds that are important in biological processes. The lethal concentration of AEADFP is above 5000 mg/L; hence, relatively safer for use in medicinal purposes.